Post Pandemic on Islamic Human Development: Study Case in Indonesia - Purbasari, Lintang Titian; Hazami, Muhammad Fikrie (INDEF - Institute for Development of Economics and Finance, 2023)
Human development cannot run properly without macro and microeconomic factors. The government's role is very important because it can regulate the flow of the economy so that, in the end, it can meet human material and non-material needs and achieve maslahah. This study aims to analyze the influence of the Gross Domestic Regional Product (GDRP), poverty rate, unemployment rate, economic function, health, and education on the Islamic Human Development Index (I-HDI) in several provinces in Indonesia. The methodology used is quantitative, with secondary data from the Central Statistics Agency (BPS) and the Ministry of Finance for 2010–2021. Data analysis method using Panel Data Regression with Random Effect Model (REM). The results of this study indicate that simultaneously the variables Gross Domestic Regional Product (GDRP), poverty rate, unemployment rate, economic, health, and education functions have a significant effect on the Islamic Human Development Index (I-HDI) in all research areas. At the same time, each variable has an influence on I-HDI except for the poverty rate and economic function. Based on these results, we provide alternative proxies to develop I-HDI and urge national and international databases and independent international Muslim organizations to start publishing proposed I-HDI for all Muslim-majority countries every year. As such, it will provide an opportunity to monitor human development across countries over time, and the I-HDI model can be improved over time. Keywords: Maqashid Syariah, Pandemic, Islamic Human Development Index, Human Development JEL: I31, O15, P46